Microstructural characteristics of gas tungsten arc synthesised Fe-Cr-Si-Ccoating - Yilmaz, O; Özenbas, M; Korkut, MH (Sage Publications Inc, 2002)
The gas tungsten arc (GTA) method was used to synthesise Fe - Cr - Si - C alloy coatings, and processing effects on the coating were investigated experimentally. Coatings were developed on an AISI type 1040 steel substrate. Four different regions were obtained in the surface coating; and in these regions either a hypoeutectic or a hypereutectic microstructure was found. The hypoeutectic microstructure consisted of primary dendrites of austenite (gamma) phase and eutectic M7C3 (M = Cr,Fe) carbides. On the other hand, the hypereutectic microstructure consisted of M7C3 primary carbides and eutectic. A hypoeutectic or hypereutectic microstructure was determined by the combination of particularly carbon concentration, solidification rate, and extent of substrate melting. The higher hardness of the hypereutectic microstructure is attributed especially to the formation Of M7C3 primary carbides. The lower hardness of the hypoeutectic microstructure is related to three effective parameters: first, the presence of, gamma phase in the primary dendrites; second, excessive dilution from the base material; and third, relatively low concentrations of chromium and carbon.
Keywords: White Cast-Iron; Coatings